2015
DOI: 10.1530/rep-14-0381
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of the prostaglandin D2 signaling pathway in reproduction

Abstract: Prostaglandins signaling molecules are involved in numerous physiological processes. They are produced by several enzyme-limited reactions upon fatty acids, which are catalyzed by two cyclooxygenases and prostaglandin synthases. In particular, the prostaglandins E2(PGE2), D2(PGD2), and F2(PGF2α) have been shown to be involved in female reproductive mechanisms. Furthermore, widespread expression of lipocalin- and hematopoietic-PGD2synthases in the male reproductive tract supports the purported roles of PGD2in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 99 publications
2
33
0
1
Order By: Relevance
“…In the “Mediterranean” pattern, there was a notably high intake of vegetable oils that were rich in omega‐6 PUFA, including linoleic acids. Linoleic acids are the precursors of prostaglandins, which are involved in follicle development, corpus luteum function, and embryo implantation . Moreover, high adherence to the “Mediterranean” pattern was positively associated with vitamin B 6 in the blood and follicular fluid, in addition to red blood cell folate.…”
Section: Discussionmentioning
confidence: 99%
“…In the “Mediterranean” pattern, there was a notably high intake of vegetable oils that were rich in omega‐6 PUFA, including linoleic acids. Linoleic acids are the precursors of prostaglandins, which are involved in follicle development, corpus luteum function, and embryo implantation . Moreover, high adherence to the “Mediterranean” pattern was positively associated with vitamin B 6 in the blood and follicular fluid, in addition to red blood cell folate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that paracetamol and some nonsteroidal antiinflammatory drugs (NSAIDs) such as aspirin and indomethacin induce endocrine disturbances in the human fetal testis capable of interfering with testicular descent (Mazaud-Guittot et al 2013). Furthermore, PGD 2 influences male germ cell differentiation in the fetal mouse testis (Moniot et al 2014), and it has been proposed that the hematopoietic PGD 2 synthase participates in the SOX9 nuclear translocation necessary for the process of Sertoli cell differentiation (Rossitto et al 2015). PG receptors have been described in Leydig cells (i.e., EP1, DP, FP, TP, and PPARg receptors; Walch et al 2003, Frungieri et al 2006, Schell et al 2007, Kowalewski et al 2009, Pandey et al 2009), Sertoli cells (e.g., EP1, EP2, EP3, EP4, DP, IP, FP, and PPARg receptors; Ishikawa & Morris 2006, Winnal et al 2007, Kristensen et al 2011, Matzkin et al 2012a, and the seminiferous tubule wall (PPARg receptors; Frungieri et al 2002a).…”
Section: Cox and Pgs In The Human Testismentioning
confidence: 99%
“…Furthermore, expression of L-PGDS protein was present in E12.5 male gonads in both Sertoli and germ cells (Moniot et al . 2009) that it is regulated upstream through either COX1 (cyclooxygenase 1) or COX2 pathways (Rossitto et al 2015). However, neither male Cox2 - nor Cox1 - knockout mice are infertile; thus, there may be multiple ways to promote production of L-PGDS in order to have a sufficient quantity of PGD2 (Gerena et al .…”
Section: What Is the Origin Of The Sertoli Cell …A Cell That Is Thougmentioning
confidence: 99%
“…NR5A1 induces initial expression of Sox9 which is then upregulated by SRY and SOX9 (Sekido and Lovell-Badge 2008) and SOX9 not only upregulates FGF9 and PTGS but it also upregulates itself (DiTacchio et al 2012). A role of both PTGS and FGF9 is to continually provide sustained expression of SOX9 (Rossitto et al 2015) (Fig. 1).…”
Section: What Happens In Vivo When Vegfa Isoforms Are Eliminated In Smentioning
confidence: 99%